Women's advocacy trainings stabilize livelihoods and build inclusive rural communities in southwestern Nigeria - Kosec, Katrina; Kyle, Jordan (CGIAR System Organization, 2024)
In many rural areas of Nigeria, women face significant barriers to economic participation, political engagement, and participation in community governance. Despite playing a crucial role in agricultural production, women often lack access to the resources, networks, and influence needed to shape their own economic futures. Structural barriers limit their opportunities to engage in advocacy, contribute to policy discussions, and assert their rights in community decision-making. Furthermore, prevailing gender norms can make it difficult for women to benefit from empowerment programs without support from their husbands or male family members. Addressing these challenges is essential to fostering more inclusive and resilient communities where women can thrive both socially and economically.